Pattern of Animal Bites and Post Exposure Prophylaxis for Rabies: An One Year Study in Bangladesh Institute of Tropical Infectious Disease (BITID) Chattogram - Rashid, Md Mamunur; Chowdhury, MA Hassan; Chowdhury, Md Hossain Rashid (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background: Rabies is a global disease occurring in more then 150 countries including Bangladesh. It was neglected in Bangladesh before 2010 with more than 2000 annual rabies case. Number of rabies patients are declining in whole world due to more availability of resources needed for rabies prevention. In this background here our objective is to study the Post Exposure Prophylaxis (PEP) in rabies & to observe the pattern of animal bites in Bangladesh Institute of Tropical and Infectious Disease (BITID) which is a national institute dealing Tropical & Infectious disease of Bangladesh. Materials and methods: It was a retrospective study carried out among bite patients coming to BITID (Both outdoor & indoor) from 01.01.2017 to 31.12.2017 where a registry of all post exposure treatment was maintained. Total 1863 cases of animal bite patients came to BITID over the study period. The data were analyzed finally. Results: Among 1836 cases, 1185(63.66%) were male and 678 (34.44%) were female. 1155 cases (62%) belonged to >12 years of age and 708 (38%) cases belonged £12 years of age 815(43.74%) cases were category III bite. 1386 (74.4%) cases were bitten by dog & bites in 1110 (59.6%) cases occurred in lower limbs. Most patients 1138 cases (61.1%) came from rural areas & maximum bites occurred from March 2017 to September 2017. Conclusion: Animal bite is a great burden for Bangladesh. To prevent it we need public awareness, mass dog vaccination, street dog control and complete post exposure prophylaxis as per schedule given by national rabies elimination program of Bangladesh government. Chatt Maa Shi Hosp Med Coll J; Vol.20 (1); January 2021; Page 51-54